Geographic, land cover and calendar month effect in on surface meteorology and insolation in coniferous forests in Mexico - Rodríguez-Moreno, Víctor M.; Ruíz-Corral, J. Ariel; Ramírez-Ojeda, Gabriela; Pérez-Miranda, Ramiro (Instituto de Ecología, A.C., 2016)
In order to demonstrate the influence of geographic location of a sampling site, land cover and calendar month on the expression of thirteen indirect indicators of surface meteorology and solar radiation, the technique of information re-scaling was applied based on latitude in order to calculate the zenith angle in coordinated pairs, in coniferous forests in Mexico. This historical series of information covers a period of 22 years of daily records. Ten sampling sites were defined in five geographical localities with two absolute land covers (natural forest and deforested) with a common spatial border; this neighboring condition was mandatory for the study. Statistical analysis revealed significant differences (p < 0.05), for land cover, sampling site and calendar month. In the expression of the indices, an apparent latitudinal effect was observed of proximity to the coastline, which seems to suggest its influence on the evaluated indexes. The results suggest the extension of the database to include direct information pertaining to meteorology (wind speed and direction) and solar radiation. These data are necessary in order to characterize the response of the land cover for spectral invariance according to variations in the radiant flow, for the ratio of reflectance, absorbance and transmittance.